LYMPHOID NEOPLASMS AFTER ALLOGENEIC HEMATOPOIETIC STEM CELLS TRANSPLANTATION. THE CASE OF SECONDARY HODGKIN’S LYMPHOMA, DIFFERENTIAL DIAGNOSIS WITH POST-TRANSPLANT LYMPHOPROLIFERATIVE DISEASE - Yu. V. Skvortsova; L. N. Shelichova; N. V. Myakova; E. R. Biyachuev; D. M. Konovalov; D. S. Abramov; M. A. Maschan; E. V. Skorobogatova; A. G. Rumyantsev; A. А. Maschan (Онкогематология)
Secondary malignant diseases are dangerous long-term complications of allogeneic hematopoietic stem cell transplantation (HSCT). This article describes the group of secondary lymphoid neoplasms and presents a rare case of secondary Hodgkin disease in a 21-year patient 6 years after HSCT due to acute myeloid leukemia. This complication should be distinguished from the Hodgkin-like posttransplant lymphoproliferative disease, because of the different therapy approaches and outcomes. We describe their main features and differential diagnostic procedures.